Factors Influencing the Turnover Intentions of Sales Staff in Telemedicine in China - Shen, Qi (2020)
Telemedicine is playing an increasingly important role in China, but there is a high turnover rate among sales staff in this industry, which have huge negative impacts on telemedicine companies. However, there are few researches on telemedicine in China, not to mention the sales personnel in this industry. Therefore, the main purpose of this study is to explore the main factors affecting the turnover intention of those employees, then propose recommendations to solve the undesirable phenomenon of high turnover from the root.